DETERMINANTS OF CUSTOMER LOYALTY IN THE BAROKAH BAKSO BUSINESS: SERVICE ETHICS AND TASTE QUALITY - Septta Aji Wilujeng; Heliyani (STMIK Indonesia Banda Aceh, 2026)
This study analyzes the influence of service ethics and taste quality on customer loyalty through customer satisfaction at Bakso Barokah Business. This study uses a quantitative approach through a survey technique on 100 customers who were designated as respondents . Data were analyzed using Partial Least Squares (PLS) through SmartPLS support . The study findings show that service ethics have a significant and positive influence on customer loyalty and satisfaction . Taste quality does not have a significant influence on customer satisfaction , but has a significant and positive influence on customer loyalty . On the other hand , customer satisfaction is proven to have a significant and positive influence on customer loyalty . The results of the mediation test show that customer satisfaction cannot significantly mediate the influence of service ethics and taste quality on customer loyalty . This finding indicates that customer loyalty is more influenced by service quality and direct customer experience with the products offered .